Correlation Between the Severity of Chronic Rhinosinusitis and Sleep Quality in Adult Patients - Clarisa Christina Gabriella; Kristanti Wanito Wigati; Budi Sutikno (Biomolecular and Health Science Journal, 2020)
Introduction: Chronic rhinosinusitis (CRS) usually accompanied by one of the symptoms (nasal obstruction, rhinorrhea) and one of associated symptoms (facial pain and/or hyposmia/anosmia). In addition, most of CRS sufferers have poor sleep quality. Thus, we aim to determine the relationship between the severity of CRS and sleep quality in adult patients.Methods: This study was cross-sectional method study. Consecutive sampling technique with estimate a proportion in finite population formula was used. The variables studied were the CRS severity based on visual analogue scale (VAS), and subjects’ sleep quality based on the Pittsburgh sleep quality index (PSQI). The data collection was carried out using a questionnaire and analyzed using chi-square test and continued with fisher’s exact test.Results: Of the 24 study subjects, 45.8% were male and 54.2% female. 83.3% had a nasal obstruction, 66.7% had rhinorrhea, 54.2% had hyposmia/anosmia, and 66.7% had facial pain. The severity of subject was mild, moderate and severe by 41,67%, 29,17%, and 41,67% respectively. 87.5% had poor sleep quality. There was no significant correlation between the severity of CRS and sleep quality (p=1,00).Conclusion: Although there was no correlation between CRS severity and sleep quality in adult patients, but CRS patients in general had poor sleep.Further study using more subjects, apply objective assessments, and include other more specific will help describe the correlation in population.